Secondary School Access Raises Primary School Achievement - Wayne Aaron Sandholtz (CESifo GmbH, 2024)
I use variation in ex-ante school fee payments to measure how Free Secondary Education (FSE) affected primary students in Tanzania. I first confirm FSE increased secondary access: secondary enrollments rose, household spending on secondary school fees plummeted, and elites' transition premium disappeared. I then show that FSE increased primary exam pass rates by 6% and secondary transition rates by 23%. This was not due to supply inputs: there was no effect on school entry, and class sizes rose. Instead it appears to be driven by demand-side investments: primary students selected into better schools, attended more, and worked less.
Keywords: I25; H52; O12; 330; school access; human capital investments; high-stakes exam data; Tanzania